Effectiveness of some herbals on initial enamel caries lesion - TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA; BİLGİN GÖÇMEN, GÜLÇİN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2016)
Objective: To evaluate the effectiveness of herbal medicaments such as ginger, rosemary and honey on remineralization of initial enamel lesion. Methods: Demineralized human enamel specimens were measured for baseline surface microhardness and fluorescence methods. Ten specimens in each of four groups were used in this in vitro recycling study with the following treatments which applied three times a day: 1) sodium fluoride toothpaste (Ipana, Procter & Gamble, Turkey), 2) ginger-honey (Arifoglu Herbals, Anzer Honey, Turkey), 3) ginger-honey-chocolate (Bind Chocolate, Turkey), 4) rosemary oil (Arifoglu Herbals, Turkey). Treatment regimens of demineralization and remineralization cycle were applied for 21 days. The post-treatment data were obtained by measurements of surface microhardness and fluorescence methods. Data were statistically analyzed by ANOVA test with Tukey's honest significant difference test. Results: Enhanced remineralization was observed with several of the treatment systems including ginger + honey and rosemary. Significant differences between treatments were observed by microhardness and FluoreCam fluorescence assesment, compared to the positive control group (NaF dentifrice). Significantly, greater remineralization was observed with the honey + ginger treatment regimen. No significant differences between groups were observed using the fluorescence assessment method, quantitative light-induced fluorescence. Conclusions: Herbals (ginger, honey and rosemary) have enhanced remineralization of initial enamel lesion.
Keywords: CACAO BEAN HUSK; IN-VITRO; STREPTOCOCCUS-MUTANS; ANTIMICROBIAL ACTIVITY; GROWTH; GLUCOSYLTRANSFERASE; THEOBROMINE; RELEVANCE; GINGER; HONEY